Construction of an IS-Free Corynebacterium glutamicum ATCC 13 032 Chassis Strain and Random Mutagenesis Using the Endogenous ISCg1 Transposase - Linder , Marten; Haak , Markus; Botes , Angela; Kalinowski , Jörn; Rückert , Christian (Frontiers in Bioengineering and Biotechnology, 2021)
Mobile genetic elements (MGEs) contribute to instability of the host genome and plasmids. Previously, removal of the prophages in the industrial amino acid producer Corynebacterium glutamicum ATCC 13032 resulted in strain MB001 which showed better survival under stress conditions and increased transformability. Still, 8 families of Insertion Sequence (IS) elements with 27 potentially active members remain in MB001, two of which were demonstrated to be detrimental in biotechnological processes. In this study, systematical deletion of all complete IS elements in MB001 resulted in the MGE-free strain CR101. CR101 shows growth characteristics identical to the wildtype and the increased transformability of MB001. Due to its improved genome stability, we consider this strain to be an optimal host for basic research and biotechnology. As a ”zero-background” host, it is also an ideal basis to study C. glutamicum IS elements. Re-sequencing of CR101 revealed that only five spontaneous point mutations had occurred during the construction process, highlighting the low mutation rate of C. glutamicum on the nucleotide level. In a second step, we developed an easily applicable ISCg1-based transposon mutagenesis system to randomly transpose a selectable marker. For optimal plasmid stability during cloning in Escherichia coli, the system utilizes a genetic switch based on the phage integrase Bxb1. Use of this integrase revealed the presence of a functional attB site in the C. glutamicum genome. To avoid cross-talk with our system and increase ease-of-use, we removed the attB site and also inserted the Bxb1 encoding gene into the chromosome of CR101. Successful insertion of single markers was verified by sequencing randomly selected mutants. Sequencing pooled mutant libraries revealed only a weak target site specificity, seemingly random distribution of insertion sites and no general strand bias. The resulting strain, ML103, together with plasmid pML10 provides a easily customizable system for random mutagenesis in an otherwise genomically stable C. glutamicum. Taken together, the MGE-free C. glutamicum strain CR101, the derivative ML103, and the plasmid pML10 provide a useful set of tools to study C. glutamicum in the future.